RNA annealing activities in HeLa nuclei. - Portman, D S (1994)
RNA-RNA base pairing plays a critical role in the interactions between pre-mRNAs and trans-acting factors during the processing of pre-mRNAs (hnRNAs) into mRNAs, and it is likely that specific factors are required to promote the annealing of RNAs. To identify particular nuclear components that have such activity, we fractionated HeLa nucleoplasm and assayed for activity which promoted the hybridization of a pre-mRNA with an antisense RNA probe complementary to 60 nucleotides (nt) encompassing the 3' splice site. At least nine major RNA annealing activities were identified and, surprisingly, eight of these copurified partially or to homogeneity with known hnRNP proteins. The activities of three of these proteins, hnRNP A1, C1 and U, were confirmed using purified recombinant proteins. Moreover, we found that the RNA binding domain alone of hnRNP C1/C2 had significant activity, indicating that this RNA annealing may result, at least partly, from chaperone activity: a direct modulation of RNA conformation by hnRNP proteins. The finding that hnRNP proteins have strong RNA annealing activity indicates that they can profoundly affect the interactions of pre-mRNAs with trans-acting factors and suggests this to be an important function of hnRNP proteins in the processing of pre-mRNAs.